2018
DOI: 10.1007/s00705-018-4071-8
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an African swine fever (ASF) vaccine strategy incorporating priming with an alphavirus-expressed antigen followed by boosting with attenuated ASF virus

Abstract: In this study, an alphavirus vector platform was used to deliver replicon particles (RPs) expressing African swine fever virus (ASFV) antigens to swine. Alphavirus RPs expressing ASFV p30 (RP-30), p54 (RP-54) or pHA-72 (RP-sHA-p72) antigens were constructed and tested for expression in Vero cells and for immunogenicity in pigs. RP-30 showed the highest expression in Vero cells and was the most immunogenic in pigs, followed by RP-54 and RP-sHA-p72. Pigs primed with two doses of the RP-30 construct were then boo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0
2

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 27 publications
2
38
0
2
Order By: Relevance
“…The C-terminal part of p30 has been identified as an immunodominant region (Murgia et al, 2019). Our results indicated that at least antigenic regions 3 and 4 are located in the C-terminal area.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…The C-terminal part of p30 has been identified as an immunodominant region (Murgia et al, 2019). Our results indicated that at least antigenic regions 3 and 4 are located in the C-terminal area.…”
Section: Discussionmentioning
confidence: 61%
“…Using mAbs derived from a p30 fusion protein expressed in Escherichia coli, a linear epitope located between amino acids (a.a.) 61-93 and conformational dependent epitopes located in the C-terminal region of p30 protein were identified (Petrovan et al, 2019). The immunodominant region of p30 was also located at the C-terminal region (Murgia et al, 2019). Further evaluation of the antigenic features of p30 protein will support development and improvement of serological assays for the diagnosis and surveillance of ASF.…”
mentioning
confidence: 97%
“…The contradictory results in this study show that immune-induced antibody responses are not necessarily proportional to protective immunity, highlighting the complexity of the role of antibody responses in anti-ASFV, and also reflecting that different adjuvants may induce different innate immune responses, which require further study and evaluation of the efficacy of neoantigens formulated in appropriate adjuvants [ 99 ]. Moreover, Murgia et al discovered that the strategy enhanced with natural attenuated strain OURT88/3 could broaden the recognition of ASFV epitopes, but its protective efficacy needs further verification [ 100 ]. In Hubner’s group, the rapid evolving genetic manipulation platform based on CRISPR/Cas9 provides a new method for screening potential immune protective antigen for more effective development of ASF virus-vectored vaccines [ 101 ].…”
Section: Current State Of Asf Vaccine Developmentmentioning
confidence: 99%
“…Pengembangan vaksin sub unit melalui rekayasa genetika dinilai aman, namun hasilnya tidak memuaskan karena hanya memberikan proteksi pada sebagian kecil ternak babi. Vaksin DNA kemudian dikembangkan, tetapi hasilnya juga kurang memuaskan karena kurang protektif (Murgia et al 2019), demikian pula dengan vaksin virus-vectored ASF. Ketiga jenis vaksin ini dinilai kurang protektif dan tidak konsisten.…”
Section: Pencegahan Penyakitunclassified
“…Oleh karena itu, akhir-akhir ini telah dikembangkan vaksin dengan menggunakan delesi gen virulen. Secara percobaan vaksin delesi gen ini dapat diharapkan, namun masih memerlukan penelitian lebih lanjut (Murgia et al 2019). Penelitian O'donnell et al (2016) melaporkan delesi gen 9GL dan MGF 360/505 pada virus virulen ASF strain Georgia 2007 akan melemahkan virulensi ASF tersebut, namun bila dibuat vaksin tidak memberikan proteksi pada uji tantang.…”
Section: Pencegahan Penyakitunclassified